Effects of dispersoid preforming via multistep sintering of oxide dispersion-strengthened CoCrFeMnNi high-entropy alloy. (20th March 2023) - Chung, SeungHyeok; Shin, Ji Ho; Ryu, Ho Jin
Highlights: A newly designed ODS manufacturing process, multi-step sintering process, consisting of a dispersoid preforming heat treatment followed by sintering to achieve the dispersoid refinement in HEA matrix was suggested. An atypical form of Y2 O3, FCC Y2 O3, formed adjacent to the dislocation inside the matrix grain during the dispersoid preforming heat treatment of multi-step sintering process with a cube-on-cube orientation relationship with the matrix. The FCC Y2 O3 formed in the multi-step sintered bulk acts as an effective obstacle to grain boundary and dislocation movement resulting in a microstructure refinement and the increment of mechanical strength. In the bulk prepared by the conventional ODS manufacturing process, coarsened dispersoids consisting of a complex structured oxide with BCC Y2 O3 as the core were predominantly formed along the grain boundary. Cr-C-O region with a crystal structure of Cr23 C6 formed in the HEA matrix serves as an oxygen-supplying reservoir for dispersoids, promoting coarsening of the dispersoids. Abstract: Dispersoid formation and microstructural evolution in an oxide dispersion-strengthened CoCrFeMnNi high-entropy alloy (HEA) using a newly designed multistep sintering process are investigated. The proposed multistep sintering consists of a dispersoid preforming heat treatment of as-milled 0.1 wt% Y2 O3 -CoCrFeMnNi high-entropy alloy powders at 800 °C, followed by sintering at 800–1000 °C under uniaxial pressure. In the conventional single-step sintered bulk, the coarsened BCC Y2 O3 dispersoids mainly form with an incoherent interface with the HEA matrix. In contrast, finer FCC Y2 O3 dispersoids, an atypical form of Y2 O3, are formed in the matrix region after multistep sintering. Nucleation of FCC Y2 O3 dispersoids is initiated on the favorable facet, the 111 plane of the austenitic matrix, with the formation of a semi-coherent interface with the matrix during the dispersoid preforming heat treatment and it maintains its refined size even after sintering. It is found that dispersoid preforming prior to sintering appears promising to control the finer dispersoid formation and refined grain structure. Graphical abstract: Image, graphical abstract